A new EMG frequency-based fatigue threshold test - Hendrix, C. Russell; Housh, Terry J.; Johnson, Glen O.; Mielke, Michelle; Camic, Clayton L.; Zuniga, Jorge M.; Schmidt, Richard J. (Journal of neuroscience methods, 2009)
Theoretically, the critical torque (CT) and electromyographic mean power frequency fatigue threshold (EMG MPFFT) describe the maximal non-fatiguing isometric torque level. The purposes of this study were two-fold: (1) to determine if the mathematical model for estimating the EMG fatigue threshold (EMGFT) from the amplitude of the EMG signal was applicable to the frequency domain of the EMG signal to estimate a new fatigue threshold called the EMG MPFFT; and (2) to compare the torque level derived from the CT test to that of the EMG MPFFT test for the vastus lateralis (VL) muscle during isometric muscle actions of the leg extensors. Nine adults (4 men and 5 women; mean±SD age=21.6±1.2yr) performed three or four continuous, fatiguing, isometric muscle actions of the leg extensors at 30, 45, 60, and 75% of maximum voluntary isometric contraction (MVIC) to determine the time to exhaustion (Tlim) values. The slope coefficient of the linear relationship between total isometric “work” (Wlim in Nms=Torque×Tlim) and Tlim was defined as the CT. Surface EMG signals were recorded from the vastus lateralis (VL) muscle during each fatiguing isometric muscle action. The EMG MPFFT was defined as the y-intercept of the isometric torque versus slope coefficient (EMG MPF versus time) plot. There were no significant differences between CT (19.7±5.8%MVIC) and EMG MPFFT (21.4±8.7%MVIC). These findings provided indirect validation of the EMG MPFFT test.